Knowledge, attitude and practice of medical and health sciences students in IIUM Kuantan regarding human papilloma virus vaccination - Al-Shami, Abdulkareem Mohammed; Elsayed, Tarek Mohamed Ali; Jamshed, Shazia Qasim; Nahas, Abdul Rahman Fata (Society of Pharmaceutical Sciences and Research, 2018)
Introduction: Human Papilloma Virus (HPV) is the major causal agent for fourth most frequent cancer in women which is cervical cancer. HPV vaccine is already available as the primary prophylactic method for cervical cancer. The objective of this study is to assess the level of knowledge, attitude and practice regarding HPV and its vaccination among medical and health sciences students in the International Islamic University Malaysia (IIUM). Materials and Methods: This study was conducted from November until December 2017. Pre-tested and validated questionnaire was distributed among third year students from faculties of medicine, dentistry, pharmacy and allied health sciences. Results: The results shows that total knowledge of students was good for medicine and dentistry student while poor for pharmacy and allied health sciences students. Medicine students showed the highest level of knowledge compared to other faculties (p=0.000016). The majority of students has a positive attitude towards HPV vaccination. Conclusion: In conclusion, the levels of knowledge and attitude of the respondents were high and positive, respectively. Small percentage of students are fully vaccinated (13.65%, 37) with no significant difference between different faculties. More awareness, healthcare programs and campaigns should be run at the campus.